EXPERIENCE WITH URISAN LONG USED IN GOUTY PATIENTS - A E Ilyina; V G Barskova (Современная ревматология, 2009)
Objective: to evaluate the safety of long-term use of Urisan. Subjects and methods. The safety of long-term (6-month) use of Urisan in 30 patients with the significant diagnosis of gout was studied. Results. Urisan was generally well tolerated. The findings suggest the drug has neither nephro- and hepatotoxicity nor negative effect on carbohydrate and lipid metabolism. Conclusion. The herbal complex Urisan has proved to be an effective and safe agent for long-term therapy in patients with gout.